Analysis of the Impact of Digital Transformation on Corporate Financial Management Efficiency - Tian, Xiaofan; Chen, Jingyu (Asia Pacific Economic and Management Review, 2026)
Against the backdrop of digital transformation, this paper explores its impact mechanisms and pathways on corporate financial management efficiency. A comprehensive evaluation framework encompassing operational efficiency, decision-making efficiency, and risk management efficiency was developed, with Haier Group serving as a case study. Findings indicate that digital transformation significantly shortens financial accounting cycles, reduces labor costs, enhances data analysis and decision-making efficiency, and strengthens real-time financial risk monitoring capabilities. Concurrently, the study identifies potential challenges during transformation, including inadequate technology adaptation, talent shortages, and data security concerns, providing theoretical and practical guidance for enterprises advancing financial management digitalization.